Fruiting plants of Bryum found in the vicinity of Syowa Station, Antarctica - Kanda, Hiroshi; Ochi, Harumi (1986)
P(論文) Fruiting plants of Bryum are recorded for the first time in the vicinity of Syowa Station, East Antarctica. These were collected at four localities along Soya Coast, namely, Rundvagshetta, Strandnibba, Einstoingen and Langhovde. specimens from the Syowa Station area were compared with those from other polar regions, especially with respect to the morphological features of peristome teeth and spores. The fruiting plant was concluded to be Bryum amblyodon C. MUELL., which is a new addition to the bryaceous flora of Continental Antarctica. departmental bulletin paper